(untitled) (Sains Humanika, 2017)
The main purpose of this research is to explore the preferable Cham script and Cham Latin; to develop application and evaluate the application products. Research sample is divided into two groups and the research instrument distributed into two forms of survey. The application was developed using ADDIE model. This survey, the acceptance of Cham script by religious group is 100%, Cham script online voting by student is 90.09%, Cham script by online questionnaire is 98.3%. EFEO Cham Latin by religious group is 100%, EFEO Cham Latin by online questionnaire is 95.4%. Viewed by sixteen experts using Fuzzy Delphi the results show that percentage of all items are 100%, more than what required (75%), the value of d for total construct is 0.02 (required â‰¤ 0.2). For conversion application, we have checked the accuracy percentage of four Cham poems and results Ariya Gleng Anak 99.88% (n=2459); Nai Mai Mang Makah 100% (n=2523); Ariya Cam Bini 100% (n=1823); Ariya Po Ceng 99.91% (n=2202). Using technologies to preserve the Cham language heritage is not only theoretically significant but also practically significant.Â Â